Bioactivity studies and chemical analysis of the medicinal herb centella asiatica (pegaga) leaves / Muhamad Haikal Azilah - Azilah, Muhamad Haikal (Faculty of Applied Sciences, 2017)
Bioactivity and chemical analysis of Centella asiatica leaves have been studied. Extraction process of C. asiatica take placed by using three different polarity of solvents which are hexane, ethyl acetate, and ethanol using cold extraction method. The highest percentage yield is ethanol crude extract which is 2.214 %. The thin layer chromatography (TLC) profile of C. asitatica leaves extracts has been identified with the best ratio of solvent system for hexane crude extract was (2:8) of hexane:chloroform. While for ethyl acetate crude extract was (7:3) of hexane:acetone. For ethanol crude extract was (1 :9) of hexane:chloroform. The most obvious separation and noticeable colour spots was shown in hexane crude extract. The phytochemical screening studies revealed that there are many secondary metabolites presence in C. asiatica such as alkaloid, flavonoid, phenol, terpenoid, glycoside, tannin, steroid, and sterol. In addition, only ethyl acetate and ethanol extracts showed antioxidant activity by using TLC bioautography technique. Antibacterial activity was tested by using disc diffusion method towards Bacillus subtilis, Staphylococcus aureus, Escherichia coli, and Salmonella typhi. The highest zone inhibition diameter was recorded in ethanol crude extract against Salmonella typhi with the zone of inhibition 13.5 mm.